Correction: Protective role of air potato (Dioscorea bulbifera) of yam family in myocardial ischemic reperfusion injury. Issue 2 (6th February 2019) - Vasanthi, Hannah Rachel; Mukherjee, Subhendu; Ray, Diptarka; Jayachandran, Karuppiah Shanmugasundara Pandian; Lekli, Istvan; Das, Dipak Kumar
Abstract : Correction for 'Protective role of air potato ( Dioscorea bulbifera ) of yam family in myocardial ischemic reperfusion injury' by Hannah Rachel Vasanthi et al., Food Funct., 2010, 1, 278–283.